An ice-binding protein from an Arctic population of American dunegrass, Leymus mollis [version 2; peer review: 3 approved] - Todd L. Sformo; James A. Raymond (F1000Research, 2020)
Several cold-hardy grasses have been shown to have ice-binding proteins (IBPs) that protect against freeze-thaw injury. Here, we looked for IBP activity in an Alaskan coastal grass, Leymus mollis (Pooidae), that had not previously been examined. Rhizome tissue had strong ice-structuring and ice recrystallization inhibiting (IRI) activities, indicating the probable presence of IBPs. The gene sequence of an IBP was obtained. The sequence encoded a 118-amino acid IRI domain composed of eight repeats and that was 80% identical to the IRI domain of the IBP of perennial ryegrass Lolium perenne. The predicted 3D structure of the IRI domain had eight beta-roll coils like those in L. perenne IBP